2020
DOI: 10.1111/infa.12329
|View full text |Cite
|
Sign up to set email alerts
|

Infant‐directed speech to infants at risk for dyslexia: A novel cross‐dyad design

Abstract: When mothers speak to infants at risk for developmental dyslexia, they do not hyperarticulate vowels in their infant‐directed speech (IDS). Here, we used an innovative cross‐dyad design to investigate whether the absence of vowel hyperarticulation in IDS to at‐risk infants is a product of maternal infant‐directed behavior or of infants’ parent‐directed cues. Interactions between mothers and infants who were at risk or not at risk for dyslexia were recorded in three conditions: when mothers interacted with (a) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 60 publications
1
4
0
Order By: Relevance
“…Thus, it would appear that mothers unconsciously adjust their vowel production to the level of their infants' linguistic competence. This is in line with studies that have demonstrated that maternal speech clarity manifested in the degree of vowel hyperarticulation is modulated by infant response to the mother (Kalashnikova et al, , 2020Lam & Kitamura, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, it would appear that mothers unconsciously adjust their vowel production to the level of their infants' linguistic competence. This is in line with studies that have demonstrated that maternal speech clarity manifested in the degree of vowel hyperarticulation is modulated by infant response to the mother (Kalashnikova et al, , 2020Lam & Kitamura, 2010).…”
Section: Discussionsupporting
confidence: 91%
“…Leong et al (2017) showed that the enhancement of prosodic amplitude modulations in IDS decreases when mothers are talking to older infants. These changes in IDS may be tied to infants' increased linguistic knowledge, as parents were shown to use more prototypically infant-directed speech when talking to infants with lower language abilities (Bohannon & Marquis, 1977;Kalashnikova et al, 2020;Reissland & Stephenson, 1999). Importantly, speech tracking was shown to increase with linguistic knowledge (Chen et al, 2020;Choi et al, 2020), meaning that infants' tracking may rely less on acoustic cues in IDS as their linguistic knowledge increases.…”
Section: Discussionmentioning
confidence: 99%
“…See for example, the MACY system that distinguishes between ‘positive and negative parenting’ based on a large set of maternal, infant, and dyadic rating scales for scoring multiple qualitative dimensions of interactive behavior ( Boeve et al, 2019 ), the Coding Interactive Behavior (CIB) for a rating scale of parent, infant, and dyadic affective states and interactive styles ( Feldman, 1998 ; Endevelt-Shapira et al, 2021 ), the Infant regulatory and maternal regulatory scoring system (IRSS and MRSS) for facial affect, direction of gaze, vocalizations, gestures, leaning, touching, self-comforting, distancing and stress ( Weinberg et al, 2008 ), maternal sensitivity and attachment ( Beebe and Steele, 2013 ), and attention, affect, orientation, touch, and composite facial-visual engagement ( Beebe et al, 2016 ). Other interesting (and more basic) parameters during parent–infant interactions can be measured as well: infant-directed speech ( Shruti et al, 2018 ; Kalashnikova et al, 2020 ), infant vocalizations (e.g., cry, fuss, yawn, and positive vocalizations, Feldman et al, 2010b ), and dyadic coordination of gaze ( Northrup and Iverson, 2020 ). These behavioral coding schemes and labels are just a few examples of the enormous number of possibilities that facilitate all kinds of behavioral coding available during parent–infant interaction.…”
Section: Analyzing Datamentioning
confidence: 99%